Relevansi Single Presence Policy dalam Menjaga Kesehatan, Ketahanan, dan Daya Saing Perbankan Indonesia Menghadapi Resesi - fahmi, wahyu; Indri Syahfitri (Journal of Law and Administrative Science, 2024)
Abstract. The Single Presence Policy (SPP) was implemented in Indonesia since 1998 with the aim of maintaining the stability and resilience of the national financial system. Amid the threat of a predicted global recession, the relevance of SPP in maintaining the health, resilience, and competitiveness of Indonesian banking becomes important to be studied. This research uses a normative juridical legal research method with a qualitative approach. Data was collected through library research and analyzed descriptively. The purpose of this research is to analyze the relevance of SPP in maintaining the health, resilience, and competitiveness of Indonesian banking in facing a recession. The research results are expected to provide input for regulators and banks in formulating appropriate policies to maintain the stability and resilience of the national financial system. Keywords: Single Presence Policy, bank health, bank resilience, bank competitiveness, recession).